How Does Serious M‐Game Technology Encourage Low‐Income Households To Perform Socially Responsible Behaviors?. Issue 4 (April 2017) - Yam, Alpha; Russell‐Bennett, Rebekah; Foth, Marcus; Mulcahy, Rory
ABSTRACT: Despite the increasing use of technology, there is little research in the marketing literature that examines how games can encourage households to achieve socially responsible behaviors such as energy efficiency. Social marketing is a subdiscipline of marketing that applies technology such as serious games in the pursuit of socially responsible behaviors. We investigate in this study how a serious mobile game (m‐game) (Reduce Your Juice) can encourage households to perform energy‐efficient behaviors by conducting group interviews with six households ( n = 17) in Brisbane, Australia. The findings reveal that households gained knowledge and were motivated and persuaded to engage in energy‐efficient behaviors as the result of the customer experience of playing the serious m‐game. We provide practitioners with implications for game design and evidence that serious m‐games can encourage group level behaviors such as household energy efficiency.